ROLE OF MEDICAL UNIVERSITY IN IMPLEMENTATION OF NATIONAL PROJECTS IN HEALTHCARE - Копытина, Наталья Валерьевна; Штернис, Татьяна Александровна; Кан, Сергей Людовикович (Medicine in Kuzbass, 2025)
The article analyzes the main target indicators and possible approaches for the effective implementation of national projects in the field of public health. The possibilities of a medical university to participate in the implementation of national projects are considered.The aim of the study is to study national projects in healthcare and develop measures for the participation of medical universities in their implementation.Materials and methods. The research material is: the national project «Healthcare» with eight federal projects, valid from January 1, 2019 to December 31, 2024; national projects in the field of public health protection valid from January 1, 2025 to December 31, 2030 «Long and Active Life», "New Health Preservation Technologies", "Family" with twenty-one federal projects. The following research methods were used: analysis of literary sources, questionnaire method, data extraction from curricula of specialties and working curricula of departments, analysis and interpretation of the obtained data.Results and their discussion. The importance of national projects in healthcare for maintaining and improving the health of the population of Russia is very great. Thanks to the national project "healthcare", the life expectancy of the population has increased, the infant mortality rate has decreased, the material and technical base has been strengthened, and extensive digitalization of healthcare has been carried out. In 2025, the implementation of three new national projects "Long and Active Life", "New Health Preservation Technologies", and "Family" began, which are a continuation of the national projects «Healthcare» and "Demography". An important role in the implementation of these projects belongs to the higher medical school. It was found that the awareness of students and medical workers studying in postgraduate training programs about national projects in the field of public health is within 60-90%, while only 44-73% of respondents are familiar with the content of the projects. The role of the medical university in the implementation of national projects in the field of public health is to inform the population about the content of the projects, their target indicators, and study national projects at the pre-graduate and postgraduate stages of training of medical personnel.In order to implement the federal project "Medical Personnel", a significant increase in recruitment to the medical and pediatric faculties is carried out, training is carried out at the level of secondary vocational and higher education in the educational programs "Nursing". Training of emergency medical workers and medical workers involved in providing medical care to patients with diabetes is being carried out.Conclusion. The proposed areas and specific measures for the participation of a medical university in the implementation of national projects in the field of public health will undoubtedly contribute to the achievement of the established target indicators. Successful implementation of new national projects will allow us to reach a higher level in the field of public health protection in our country, will enable every citizen to receive affordable and high-quality medical care, promote health and improve the well-being of people.
Keywords: national projects in healthcare; federal projects; postgraduate education; curricula; training programs